Uma sequência didática para o ensino da espectroscopia no ensino médio por meio da experimentação - Silva, Everaldo Mateus da (2020)
With the scientific and technological advances pervading our daily lives, the teaching of Physics has been undergoing changes, among which, the inclusion of contents of Contemporary and Modern Physics (CMP) in high school. Through a perspective of a more enjoyable and interactive approach to these concepts, this work aimed at creating an educational object on the mercury- vapor bulb spectrums and the resistance bulb, seeking to provide a more meaningful learning experience through practical activities. The teaching methodology is grounded on the Meaningful Learning Theory by Ausubel and the theoretical framework is based on the numerous works by Moreira. The study was carried out with two classes of high school students in their senior year: one Test Class (TC) and one Control Class (CC). The instructor developed traditional lessons for both classes with initial assessment of learning. Later, the instructor worked with the CC and applied the educational product in the TC for a new assessment and comparison between classes. The purpose of the educational product for use and handling by the students was to facilitate and strengthen the concepts previously studied by them as well as their acquisition of new concepts. The educational product allowed the understanding of concepts regarding atomic spectroscopy (emission spectrums and absorption and continuous and discrete spectrums). At first, in CC and TC, student participation was the same as observed in traditional classes taught by the author. However, in TC, most students were motivated and challenged when performing experimental procedures and the proposed activities. Significant advances can bee observed, with students better expressing their ideas through meanings and justifications in discursive questions. Overall, we have noted improved answers to questions regarding the proposed procedures of the educational product.